Penerapan Kaidah-Kaidah Hukum Islam dalam Istinbath Hukum (Analisis Kajian Dewan Hisbah/Persis) - Syamsul Bahri (Universitas Syiah Kuala, 2011)
ABSTRACT: The principles of Islamic law are fundamentals that can be an operational reference in finding Islamic law which is a study to ease Islamic thinkers in researching and finding a law that has not ever been ruled. It is required in terms of overcoming the worries of Muslems in deciding wrether a matter can be done or not on daily life. Generally it covers the case and problem recently, such as the use of urine as medicine, cheque etd responding such matter. Persis as one of community associations of muslems in Indonesia, through its assembly board of hisbah does the draft and research in order to find the law from a daily problem. The process of law finding is done by looking at the especial pinciples. In addition, it should refer to al-Quran and as-Sunnah first. The Implementation of Islamic Principles in Finding Law (Analysis Hisbah/Persis Board)